MANAJEMEN LAYANAN KONSELING INDIVIDUAL DALAM MENINGKATKAN KEMATANGAN KARIR SISWA KELAS XII DI SMAN 1 MENGANTI - Mardiana, Tri; Amrozi Khamid; Kaniati Amalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abstract This study aims to determine the role of individual counseling service management in improving career maturity of grade XII students at SMAN 1 Menganti Gresik. Career maturity is an indicator of an individual's readiness to make decisions related to career choices and can affect students' success in planning their future. Meanwhile, individual counseling services have a very important role in supporting the development of students' career maturity through a personal approach that helps students understand their potential, interests, and career choices that are in accordance with their background and abilities. The research method used is a qualitative approach with a descriptive research type. Data collection techniques were carried out through in-depth interviews, observations, and documentation of grade XII students, supervising teachers, and principals. The data obtained were then analyzed using a descriptive analysis techniques. The results showed that individual counseling services at SMAN 1 Menganti Gresik had a positive impact on improving students' career maturity. Students who participated in counseling services felt more confident in determining career choices and were better able to understand their potential. In addition, this service also helped students overcome confusion and anxiety related to their future careers. Several factors that influenced the success of counseling services included the involvement of competent counselors, support from parents, and good communication between students and counselors. Based on these findings, it is recommended that schools continue to optimize individual counseling services by improving counselor competence, expanding access to career-related information, and involving parents in the counseling process to support the development of students' career maturity. Improving counseling service facilities and infrastructure is also needed to create a supportive environment for students in planning their future.